Analysis of the Impact of Artificial Intelligence (AI) on the Public’s Interest in Visiting the Solok City Public Library - Dodi Nofri Yoliadi; Wahyu Imamy Putri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Analysis of the Impact of Artificial Intelligence (AI) on the Public’s Interest in Visiting the Solok City Public Library” aims to describe the impact of Artificial Intelligence on visiting interest at the Solok City Public Library, as well as the role of Artificial Intelligence (AI) in shaping the ways of thinking, feelings, and actions of library users regarding their visits. This study applies DeLone and McLean’s Information Systems Theory and Walgito’s Theory of Perception. The research design used is qualitative with a descriptive approach. Data sources were obtained from both primary and secondary data. Data collection techniques consisted of observation, interviews, and documentation. The data analysis techniques included data reduction, data presentation, conclusion drawing, and verification. Data validity was ensured through source triangulation, time triangulation, and technique triangulation. The results of this study indicate that the use of Artificial Intelligence (AI) has not shown a direct influence on users’ interest in visiting the Solok City Public Library; rather, AI functions as a supporting tool in the initial information-seeking process. In shaping their ways of thinking, users feel that AI facilitates searching, but they still appreciate the role of the library. From an emotional perspective, they enjoy using AI but continue to verify information through the library. In terms of actions, the use of AI does not reduce their interest in visiting the library, as the library is still regarded as a comprehensive source of information and a place for learning.